1976
DOI: 10.1128/aac.9.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of the Polyene Antibiotic Candicidin: Binding Factors in the Wall of Candida albicans

Abstract: The polyene antibiotic candicidin produces a rapid efflux of K + ions from a suspension of Candida albicans . Onset of K + leakage depends on the culture age, stationary-phase yeasts leaking K + more slowly than exponential-phase yeasts. The time taken for potassium leakage to begin represents the time taken by the antibiotic to cross the cell wall and produce membrane damage. It was shown that there were factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…3). On the basis of the absorbance of the peaks, we could be certain that L and C had <10% of the ergosterol content of C. albicans B311, which contained a standard level (8).…”
Section: Resultsmentioning
confidence: 99%
“…3). On the basis of the absorbance of the peaks, we could be certain that L and C had <10% of the ergosterol content of C. albicans B311, which contained a standard level (8).…”
Section: Resultsmentioning
confidence: 99%
“…Although candicidins are highly active antifungals, their medical use is restricted to severe cases (28). Like other polyketide polyenes, candicidins interact with sterols in the fungal cell membranes, causing K ϩ -leakage and inducing cell death (29). The relatively rare development of resistance to polyketide polyenes among pathogenic fungi (28) might explain why leaf-cutting ants benefit from the presence of candicidinproducing microorganisms and do not face the risk that Escovopsis will adapt quickly.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the receptors for the nontoxic binding are fatty acids located in the cell wall of C. albicans (5). Others have shown that polyenes can bind to fatty acids (2,5), but it is worth noting that whereas both sterols (3) and fatty acid (6) (8,12). In an experiment similar to the one described for AmB, low concentrations of miconazole induced an increase in colony-forming units comparable to that caused by the polyene antibiotics (data not shown).…”
mentioning
confidence: 99%